(untitled) (Journal of the College of Basic Education, 2023)
The language of the Holy Qur’an is the language of eloquence and eloquence that the Arabs failed, ﮣ ﮤ ﭼ (Al-Shu’ara’: 195), and this language is subject to rules, controls and provisions for reading and pronouncing it, including how to produce the letter and pronounce it, and the adjective with which it comes out according to its location and its interdependence in The word to form sentences, in addition to the existence of provisions for that, and all of these things make the Arabic language its splendor and distinction among the rest of the languages, as well as being the language of the Noble Qur’an, and with the development of man and what happened to this Arab nation as a result of many difficult and compelling circumstances, the Arabic language began to decline and the use of words An outsider, while the Holy Qur’an remained preserving its eloquence and eloquence.In the universities of Iraq, the Arabic language is taught extensively, but in colleges and institutes of fine arts and in most of their specializations, the student (artist) studies the process of pronouncing it, and under several names, including (voice and diction), because There is an urgent need for sound pronunciation to be convincing and influencing the viewer, whether it is in theatre, cinema or television.The researcher noticed the weakness represented in the performance of teachers and teachers of art education in the classroom in pronouncing the Arabic letters and speaking eloquently, which he found By practicing this profession for a period of not less than five years, and also observing artworks within the departments of the College of Fine Arts, especially the Department of Art Education, which is represented by a weakness in the pronunciation of the Arabic letter (a way out and an adjective), and according to the researcher’s knowledge of the subject of sound and diction, and the interviews conducted by the researcher with Teaching this subject, the researcher did not find any practical academic study in the departments of the College of Fine Arts - University of Baghdad, in the subject of sound and diction, concerned with the exits and descriptions of letters in a detailed manner and its skillful performance, or the use of what is taught in the science of intonation curricula of exits, recipes and rulings, so the researcher identified the problem of his research With the following question: (Is it possible to develop the performance capabilities of the students of the Department of Art Education in the subject of voice and diction (characteristics of letters) through an educational program).